TINGKAT PARTISIPASI MASYARAKAT TERHADAP KEBERADAAN LUBUK LARANGAN TEBAT DI DUSUN TEBAT KECAMATAN MUKO-MUKO BATIN VII KABUPATEN BUNGO PROVINSI JAMBI - Adinda Ayu Lestari; Rini Hertati; Muhammad Natsir Kholis (SEMAH Jurnal Pengelolaan Sumberdaya Perairan, 2022)
Waters conservation areas provide many benefits for human life. Therefore,it is necessary to carry out comprehensive management by various parties in order to reduce damage with the principles of sustainable development, one of which isby developing river area protected. The river area protected (RAP) Tebat which islocated in Tebat Village was formed in the 90s, the formation of the river area protected is inseparable from community participation. This study aims todetermine the level of community participation and to find out how the process of forming the river area protected. The research method is a survey, with randomsampling and purposive sampling data. The results showed that the level ofcommunity participation to the existence of river area protected was 63.9 % (low category). The process for the formation river area protected is through deliberationfrom the community to closed the river area protected, opened the river area protected, determine rules/sanctions and a supervisory system